Current state of knowledge and concerns regarding cardiopulmonary resuscitation performed in the setting of out-of-hospital sudden cardiac arrest among adult, non-medical rural residents - Budzyńska, Julia; Kozioł, Ilona; Leśniewska, Magdalena; Szaniawska, Monika; Szast, Konrad (Journal of Education, Health and Sport, 2022)
INTRODUCTION Every year in Poland 56,000 outside the hospital there is a sudden cardiac arrest. OBJECTIVES The aim of the study was to determine the level of knowledge of basic life support undertaken in prehospital management in rural areas. The second objective of the study was to assess needs for cardiopulmonary resuscitation(CPR) training among adults in rural areas. MATERIAL AND METHODS The study was carried out with the use of an original questionnaire based on the review of literature and guidelines of the European Resuscitation Council. The questionnaire was shared by social media. The questionnaire consisted of the following parts: metric, experience of previous CPR, knowledge about CPR, assessment of demand and interest in expanding knowledge and skills in CPR. A total of 501 responses were collected, of which 316 from adult, non-medical rural residents were analyzed. RESULTS Over 85% of respondents knew how to assess consciousness of the victim, 95% of respondents knew when to start CPR. About 33% of the respondents did not know the correct location of chest compressions. Moreover 65% of them could not identify the correct frequency of compressions. Although rib fracture was one of the most commonly cited concerns, it was a potential reason to discontinue CPR only for 4.5% of respondents. CONCLUSIONS It was observed that there is a need for additional CPR training among rural adult residents. The information collected in this study may allow for the planning of appropriate educational activities to increase the level of knowledge about CPR in heart accidents.